2020
DOI: 10.1093/ofid/ofaa275
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Use of HIV Pre-exposure Prophylaxis Among Men Who Have Sex With Men During the COVID-19 Pandemic in Melbourne, Australia

Abstract: Abstract We surveyed 204 MSM who were PrEP users. One in four daily PrEP users stopped taking PrEP during the COVID-19 pandemic and 5% switched to on-demand PrEP. Most men reduced PrEP use because they stopped having casual sex and reduced the number of casual partners during the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 11 publications
5
81
1
Order By: Relevance
“…Among the MSM using PrEP before the lockdown period, 47.0% had stopped using PrEP, which is in line with a study among MSM in Australia. 19 While it cannot be excluded that they stopped using PrEP to ensure sufficient pill supplies, only 8.0% in our study reported being concerned about not having sufficient pills. Moreover, considering that almost two-thirds had been on a PrEP care appointment within 90 days before completion of the survey and that only 22.6% had their appointment postponed, it is unlikely that they stopped using PrEP due to not having access to PrEP care.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Among the MSM using PrEP before the lockdown period, 47.0% had stopped using PrEP, which is in line with a study among MSM in Australia. 19 While it cannot be excluded that they stopped using PrEP to ensure sufficient pill supplies, only 8.0% in our study reported being concerned about not having sufficient pills. Moreover, considering that almost two-thirds had been on a PrEP care appointment within 90 days before completion of the survey and that only 22.6% had their appointment postponed, it is unlikely that they stopped using PrEP due to not having access to PrEP care.…”
Section: Discussioncontrasting
confidence: 59%
“…This is in line with studies in the USA and Australia where MSM indicated fewer sexual partners or having less opportunities for having sex. [17][18][19] The reduced sexual activities with sexual partners outside the household is likely to result in reduced HIV and STI transmission among MSM. Among those who had sex with non-steady partners during the lockdown in our study, more than two-third were using PrEP or were HIV positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 For some men, stopping sex with nonprimary partners may obviate the need for PrEP. 15 , 22 Conversely, some GBM may prefer to continue their PrEP use as discontinuation may undermine the habit of pill-taking, the reassurance of being protected from HIV, or inhibit their motivation to reinitiate. Some men also seem to believe that PrEP may offer some protection against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in PEP prescriptions we saw was slightly lower than that seen at 56 Dean Street, which might be because the COVID-19 epidemic in England (5585 cases as of March 22) 2 was larger than in Australia (1765 cases as of March 22). 3 The reduction observed at MSHC might have been due to reduced sexual risk during the COVID lockdown period rather than reduced access to services, 4 given our walk-in service remained open and accessible throughout the period.…”
mentioning
confidence: 99%